Induction of labor in women with unfavourable cervix: comparison of efficacy of intracervical Foley catheter with PGE2 gel - Gupta, Shilpa; Kagathray, Bhumika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The aim of our study was to compare the efficacy, safety and patient’s satisfaction of intracervical Foley catheter with intracervical dinoprostone gel (PGE2 gel) for cervical ripening for successful induction of labor. Methods: Prospective study was conducted in Department of Obstetrics and Gynaecology, M P Shah Medical College, Jamnagar, Gujarat. 317 women with term pregnancy with bishop score of less than 4 with various indications for induction were included. Intracervical foley catheter was kept in 162 women for cervical ripening (group A) while intracervical PGE2 gel was kept in rest 155 women (group B). The change in the bishop score, progress of labor, adverse effects and outcome of labor along with the patient’s satisfaction were assessed. Results: With regard to the obstetrical parameters, the two groups were comparable with respect to maternal age, gestational age, parity, indication for induction and initial bishop score. At 12 hours, both the groups showed significant improvement in bishop score, 5.2±1.81 and 4.8±1.76 in Foley catheter and PGE2 gel respectively. Mean induction to delivery interval was 18.8±5.5 in group A and 17.9±5.3 in group B, which was statistically insignificant. No significant differences in side effects, mode of delivery and APGAR score were noted in both the groups. However, the incidence of hyperstimulation and tachysystole was higher in PGE2 gel group. Conclusions: This study shows that both Foley catheter and dinoprostone gel appear to be equally effective agents for cervical ripening. Infect foley catheter is cheap, causes less fetal distress and is safer than PGE2 gel.